2017
DOI: 10.2147/dddt.s140644
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine reduces the neuronal apoptosis related to cardiopulmonary bypass by inhibiting activation of the JAK2–STAT3 pathway

Abstract: Cardiopulmonary bypass (CPB) constitutes one of the primary methodologies pertaining to cardiac surgery. However, this form of surgery can cause damage to the body. Many studies have reported that dexmedetomidine confers cerebral protection. In this study, we aimed to investigate the effect and mechanism of dexmedetomidine on neuronal apoptosis caused by CPB. Here, rats were treated with different doses of dexmedetomidine by intravenous infusion 2 hours after CPB. We observed that dexmedetomidine treatment to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…These findings suggest that propofol, midazolam and dexmedetomidine are effective and safe for the sedative treatment of ICU patients with sepsis, but dexmedetomidine has the best effect. This is similar to the findings of Chen et al (23) and Sonneville et al (24), both of which support the results of this study. There was no difference in HR among the three groups, suggesting that the three sedation methods had the same effect on patients' cardiac function.…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest that propofol, midazolam and dexmedetomidine are effective and safe for the sedative treatment of ICU patients with sepsis, but dexmedetomidine has the best effect. This is similar to the findings of Chen et al (23) and Sonneville et al (24), both of which support the results of this study. There was no difference in HR among the three groups, suggesting that the three sedation methods had the same effect on patients' cardiac function.…”
Section: Discussionsupporting
confidence: 93%
“…Dexmedetomidine is a α 2 adrenoceptor agonist first licenced for clinical use in 1999 by FDA, with an initial use for sedation. In animal models of SIRS and surgical insult, dexmedetomidine has been shown to reduce the severity of neuroinflammation and neuroapoptosis [ [82] , [83] , [84] , [85] , [86] ]. Dexmedetomidine administration is associated with reduced hippocampal expression of IL-1β, IL-6, TNF-α and TLR-4, as well as reduced astrocyte and microglial activities [ 83 , 87 ].…”
Section: Therapeutic Options For Post-operative Neurological Complicamentioning
confidence: 99%
“…In an experimental study, Sancaktar et al reported that there was a signifi cant decrease in renal apoptotic index in the DEX group compared to the I/R damage group (29). Again Chen et al showed that use of DEX reduces apoptosis in cardiopulmonary bypass related neuronal apoptosis (31). In another experimental study, Cakir et al reported that DEX has been shown to reduce histological damage on large tubular necrosis and glomerular damage secondary to I/R injury (32).…”
Section: Discussionmentioning
confidence: 99%